Determining virological suppression and resuppression by point-of-care viral load testing in a HIV care setting in sub-Saharan Africa. (January 2020) - Villa, Giovanni; Abdullahi, Adam; Owusu, Dorcas; Smith, Colette; Azumah, Marilyn; Sayeed, Laila; Austin, Harrison; Awuah, Dominic; Beloukas, Apostolos; Chadwick, David; Phillips, Richard; Geretti, Anna Maria
Abstract: Background: This prospective pilot study explored same-day point-of-care viral load testing in a setting in Ghana that has yet to implement virological monitoring of antiretroviral therapy (ART). Methods: Consecutive patients accessing outpatient care while on ART underwent HIV-1 RNA quantification by Xpert. Those with viraemia at the first measurement (T0) received immediate adherence counselling and were reassessed 8 weeks later (T1). Predictors of virological status were determined by logistic regression analysis. Drug resistance-associated mutations (RAMs) were detected by Sanger sequencing. Findings: At T0, participants had received treatment for a median of 8·9 years; 297/333 (89·2%) were on NNRTI-based ART. The viral load was ≥40 copies/mL in 164/333 (49·2%) patients and ≥1000 copies/mL in 71/333 (21·3%). In the latter group, 50/65 (76·9%) and 55/65 (84·6%) harboured NRTI and NNRTI RAMs, respectively, and 27/65 (41·5%) had ≥1 tenofovir RAM. Among 150/164 (91·5%) viraemic patients that reattended at T1, 32/150 (21·3%) showed resuppression <40 copies/mL, comprising 1/65 (1·5%) subjects with T0 viral load ≥1000 copies/mL and 31/85 (36·5%) subjects with lower levels. A T0 viral load ≥1000 copies/mL and detection of RAMs predicted ongoing T1 viraemia independently of self-reported adherence levels. Among participants with T0 viral load ≥1000 copies/mL, 23/65 (35·4%) showed resuppression <1000 copies/mL; the response was more likely among those with higher adherence levels and no RAMs. Interpretation: Same-day point-of-care viral load testing was feasible and revealed poor virological control and suboptimal resuppression rates despite adherence counselling. Controlled studies should determine optimal triaging modalities for same-day versus deferred viral load testing. Funding: University of Liverpool, South Tees Infectious Diseases Research Fund